Posisi Hassan dalam Reform Islam di Indonesia - Syafiq A. Mughni (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
The progress of Hassan's attitude and thinking has prompted Muslims to revisit every custom and tradition that has been considered to be well established and taken for granted, as adopted by